2007
DOI: 10.3892/ijmm.19.1.113
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinase subtypes and Akt regulate diosgenin-induced apoptosis of rheumatoid synovial cells in association with COX-2 expression and prostanoid production

Abstract: Abstract. In the present study, we investigated the signalling pathways involved in diosgenin-induced apoptosis in human rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS) in vitro with particular interest on Akt and MAPKs activation in relation to arachidonic acid metabolism via COX-2 pathway. MAPK activation was measured by ELISA quantification in diosgenin-treated human RA FLS. Expression of Akt and phospho-Akt was analyzed by Western blot analysis. Nuclear factor-κB (NF-κB) translocation was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…At this stage of our study, we showed that three structurally similar saponins caused apoptosis of synovial cells but with different signalling pathways compared with results previously described for diosgenin (28) where three MAPK pathways were implicated; hecogenin or tigogenin induced apoptosis only by the p38 pathway. To confirm the implication of the p38 kinase signalling pathway in hecogenin-or tigogenininduced apoptosis in human RA FLS, we used a specific inhibitor for pretreatment before addition of saponins.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…At this stage of our study, we showed that three structurally similar saponins caused apoptosis of synovial cells but with different signalling pathways compared with results previously described for diosgenin (28) where three MAPK pathways were implicated; hecogenin or tigogenin induced apoptosis only by the p38 pathway. To confirm the implication of the p38 kinase signalling pathway in hecogenin-or tigogenininduced apoptosis in human RA FLS, we used a specific inhibitor for pretreatment before addition of saponins.…”
Section: Discussionmentioning
confidence: 50%
“…Diosgenin induced apoptosis in human RA FLS by inhibition of ERK activation but also by activation of p38 and JNK (28). However, in the absence of the 5,6-double bond in their structures, we demonstrated that only the p38 pathway was implicated in hecogenin-and tigogenin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…52 Combined association implicating a MEK inhibitor (U0126) and diosgenin is the most effective in inducing very strong apoptosis with down-regulation of COX-2 expression and activity in human RA FLS. 53 Diosgenin induced megakaryocytic differentiation of HEL cells through a combined activation of ERK and inhibition of the p38 MAPK pathways. Inhibition of ERK activation by a MEK inhibitor abrogated diosgenin-induced differentiation.…”
Section: Effect Of Diosgenin On Cancermentioning
confidence: 99%